The relationship between anthropometry and biomotor ability on gymnastics potential at SD Negeri 1 Gentan - Baskoro Bisma Yoga; Ria Amelia Karo Karo; Tsadila Marchlusiana; Elisa Putri Arsi; Elmalia Virdania Putri; M. Luqman Ahda; Muhammad Fakhri; Muhammad Irvan Eva Salafi; Abdul Alim; Herwin; Okky Indera Pamungkas; Ari Iswanto; Ridho Gata Wijaya; Wisnu Nugroho; Muhammad Wahyu Arga (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2025)
This study aims to analyze the relationship between anthropometric variables and biomotor abilities with gymnastics potential in elementary school students. The research method used a correlational quantitative approach involving 106 fourth and fifth grade students aged 9–11 years at SD Negeri 1 Gentan. Data were collected through anthropometric measurements (height, weight, arm span, sitting height) and biomotor ability tests (flexibility, core muscle strength, coordination). Data analysis was performed using Pearson's correlation test and multiple regression using SPSS. The results of the study showed that: (1) Height was significantly correlated with arm span (r = 0.687; p < 0.01) and sitting height (r = 0.434; p < 0.01), but not with biomotor ability; (2) Sit height has a positive relationship with core muscle strength (plank) (r = 0.346; p < 0.01), while arm span has a negative correlation (r = -0.209; p < 0.05); (3) Biomechanical abilities such as flexibility (split) and body rotation (air turn) are significantly correlated (r = 0.775 and r = 0.676; p < 0.01), but are not directly influenced by anthropometric variables. The conclusions of this study indicate that gymnastics potential is more influenced by technical training and flexibility than by body structure, although certain anthropometric variables such as sitting height and arm span play a role in core muscle stability. The implications of this study highlight the importance of combining anthropometric monitoring with structured biomotor training programs for the development of gymnastics potential in elementary school students. Keywords: Anthropometry, Biomotor, Gymnastics, Elementary School, Talent Guidance.